Réponses

2013-09-05T23:54:19+02:00
(x² − 25) + (x − 5) (2x + 5)  =  x² − 5² + (x − 5) (2x + 5)
                                           =  (x − 5) (x + 5) + (x − 5) (2x + 5)
                                           =  (x − 5) (x + 5 + 2x + 5)
                                           =  (x − 5) (3x + 10)

   car     a² − b²  =  (a − b) (a + b)



 


(2x + 1)² + (2x + 1) (4x + 3)  =  (2x + 1) (2x + 1) + (2x + 1) (4x + 3)
                                             =  (2x + 1) (2x + 1 + 4x + 3)
                                             =  (2x + 1) (6x + 4)